Determination of Evidence Evaluation of Individual Characteristics Used in Handwriting Analysis According to the Frequencies in Database - Öner, Dilara; Cengiz, Salih; Çetin, Gürsel (The Bulletin of Legal Medicine, 2017)
Objective: The aim of the study is to determine the reliability of the results gained from the hand-writing investigations and comparisons mathematically by using likelihood ratios in order to form a database.Materials and Methods: For this purpose, 500 people graduated from university or post-graduate institutions or still studying, were used to write the letters and numbers one by one and a special text containing all the letters and numbers with punctuation and connections, twice. All the written samples were scanned with high resolution and transferred to a computer.A sentence which has a criminal offense were written in an effort to escape without changing some of the letters by different individuals. Three experts who are not authored in this publication were offered to compare the sentences with the collected samples and to determine the characteristics that will show belonging.Results: The similarities for the construction and forms of the letters that were determined by the experts were searched in database, and the frequencies of these similarities in databases and society were determined to elucidate the mathematical reliability of the results obtained from the study.Conclusion: In recent years, there are lots of scientific studies related with this topic and this study was performed under the light of these studies. Some characteristics determined as similarity were highly seen in the Database whereas some characteristics were rarely seen. As a result, it was concluded for an expert it has a great importance that he or she should use either a general database or create a database from the archived samples.
Keywords: Document Examination; Handwriting Comparisons; Database; Likelihood Ratio; Evidence Evaluation